Frequency of tumors in dogs based on cytological diagnosis: a retrospective study in a veterinary teaching hospital - Rossetto, Victor José Vieira; Moreno, Kleber; Grotti, Claudia Bosselli; Reis, Antonio Carlos Faria dos; Bracarense, Ana Paula Frederico Rodrigues Loureiro (Semina: Ciências Agrárias, 2009)
Cytological examination is considered a very important method to diagnose neoplasms in pets and can be performed in many clinical situations. The aim of this study was to determine the prevalence of neoplasms diagnosed by cytological examination in dogs from the region of Londrina, and to evaluate epidemiological aspects as age, breed, sex predisposition, biological behaviour and anatomical localization. The data were obtained from the Animal Pathology Laboratory of Universidade Estadual de Londrina. 3378 cases of cytological examinations from the routine service of the laboratory were evaluated, from January 1996 to December 2006. From these, 1019 cases were diagnosed as neoplasms. Round cell tumors represented 44% of the diagnosis, followed by epithelial and mesenchymal neoplasms with 36.7% and 16%, respectively. Undifferentiated neoplasms totalized 3.3% of the cytological diagnosis. Malignant behaviour were more frequent in epithelial than mesenchymal neoplasms. Mast cell tumor, transmissible venereal tumor and lymphoma were the neoplasms more frequently diagnosed within round cell tumors. Pure breeds were more prevalent than mongrel dogs. Boxers, poodles and German shepherds were the most affected by neoplasms. The average age was 7.94 Â± 3.55 years. There was no sex predisposition. Perineum was the most affected site in benign epithelial neoplasms and transmissible venereal tumors, whereas benign mesenchymal neoplasms were often located in thorax. Malignant epithelial and mesenchymal neoplasms, melanoma and histiocytoma were located mainly in the head. Mast cell tumors were observed mainly in trunk and limbs. The most common clinical sign in lymphoma was lymphadenomegaly.